Space Identity in Vyborg: Analysis of Street and Food Services Names - L. S. Zhirnova (Сравнительная политика, 2015)
Th e names of streets and food services mostly refl ect the peculiarities of geostrategic location of Vyborg. Government-appointed street names remind the citizens of the military past and its belonging to Russia, and the names of cafes and restaurants refer to Europe, which indicates that European identity is the most preferable for inhabitants.